Talking Circle: FSKM Colloquium (02/2022) / Nadiah Mohamed, Nurul Aityqah Yaacob and Nor Ashikin Sahrom - Mohamed, Nadiah; Yaacob, Nurul Aityqah; Sahrom, Nor Ashikin (Universiti Teknologi MARA, Negeri Sembilan, 2022)
The Department of Computer Science & Mathematics (FSKM), UiTM Negeri Sembilan Kampus Kuala Pilah has organised the Talking Circle: FSKM Colloquium (02/2022) on August 24, 2022. This colloquium was held online using the Google Meet platform which starts from 10 amto 11 am. There are two presenters involved in this colloquium. The first presentation was entitled "Depth Value Estimation Based on Triangulation Geometry and Perspective Projection" by Intan Syaherra Ramli. The sharing was about depth value estimation using triangulation geometry and perspective projection for 3D reconstruction from multi-view photographs. The results demonstrate that the proposed method gives accurate results for all subjects compared with other alternative methods. This method utilized several photos to make a precise, quick, and less complex 3D reconstruction.